Does health workforce density improve health outcomes in a country? - AMARASINGHE, Muditha Chathuranga (KDI School, 2016)
Health Human Resources are the cornerstone of health care provision around the world. Their availability, ability, & commitment are imperative to bring out the desired health outcomes of a country. Health Human Resources are not uniformly distributed around the world. Even within countries there are un-even distributions of health human resources. Since Health Human Resources are directly in contact with people who seek care, they are mostly related to the desired health outcomes of a country. There are number of studies that show a relationship between Health Human Resources & Health Outcomes. Defining as the number of health workers for ten thousand people, health workforce density is the most commonly measured health workforce indicator. In this study, relationships between health human resource density and health outcomes have been assessed choosing five countries in South Asia region considering literacy, income, and health care expenditure abilities. Within the country, Sri Lanka shows a wide variation of distribution of human resources, so as health outcomes. Most of the health outcomes were related to health workforce density although it was not the case at all the time. While comparing Sri Lanka with four other countries in the region namely India, Pakistan, Bangladesh, and Maldives it is evident that there are variations in health human resources & health outcomes. While Maldives is showing better health outcomes with high density of human resources, Pakistan showed poor outcomes with low density of health workers. Sri Lanka is exceptional to show better outcomes even with low density of human resources. While assessing other related factors, it was evident that health outcomes were related not only to health workforce density, but also to adult literacy, Per-capita income and Total Health Expenditure (THE) per-capita. High Literacy, High GNI per-capita, and high THE per-capita was associated with better health outcomes.
Thesis(Master) --KDI School:Master of Public Management,2016